IP convergence : the next revolution in telecommunications - Muller, Nathan J. (Artech House telecommunications library., 2000)
This manual approaches the combination of voice, video and data within the new communications paradigm of IP convergence and examines how these different types of communication will be delivered to any environment from LAN to WAN at much less cost and complexity than either ISDN or ATM. Featuring references to important IP convergence-related Web sites throughout, this book provides comprehensive information on the technologies that will make convergence possible, and it examines the benefits, applications, vendor approaches, migration strategies, and regulatory issues that will affect this new technology. It also covers how IP convergence will affect LAN and WAN networks, and how you communicate at home and in the office. It discusses why implementation of full convergence can happen only when a host of major issues are addressed, including how to place Internet calls to conventional telephones in existing networks and infrastructure improvement and management of Internet call centres.